Microbiomes associated with bovine periodontitis and oral health - Borsanelli, Ana C. [UNESP]; Lappin, David F.; Viora, Lorenzo; Bennett, David; Dutra, Iveraldo S. [UNESP]; Brandt, Bernd W.; Riggio, Marcello P. (Elsevier, 2018)
Periodontitis is an infectious polymicrobial, immuno-inflammatory disease of multifactorial aetiology that has an impact on the health, production and welfare of ruminants. The objective of the present study was to determine the microbial profiles present in the gingival sulcus of cattle considered periodontally healthy and in the periodontal pocket of animals with periodontitis lesions using high-throughput bacterial 16S rRNA gene sequencing. Subgingival biofilm samples were collected from 40 cattle with periodontitis and 38 periodontally healthy animals. In total, 1923 OTUs were identified and classified into 395 genera or higher taxa. Microbial profiles in health differed significantly from periodontitis in their composition (p < 0.0001, F = 5.30; PERMANOVA) but no statistically significant differences were observed in the diversity of healthy and periodontitis microbiomes. The most prevalent taxa in health were Pseudomonas, Burkholderia and Actinobacteria, whereas in disease these were Prevotella, Fusobacterium and Porphyromonas. The most discriminative taxa in health were Gastranaerophilales, Planifilum and Burkholderia, and in disease these were Elusimicrobia, Synergistes and Propionivibrio. In conclusion, statistically significant difference exists between the microbiome in bovine oral health and periodontitis, with populations showing 72.6% dissimilarity. The diversity of the bacteria found in health and periodontitis were similar and bacteria recognised as periodontal pathogens showed increased abundance in disease. In this context, the main components of bacterial homeostasis in the biofilm of healthy sites and of dysbiosis in periodontal lesions provide unprecedented indicators for the evolution of knowledge about bovine periodontitis.
Keywords: Bacteria; Cattle; High-throughput sequencing; Microbiome; Periodontal disease